INCREASING STUDENTS’ WRITING ABILITY AT DESCRIPTIVE TEXT BY USING BITS AND PIECES GAME AT EIGHT GRADE OF MTS PAB 1 HELVETIA MEDAN - Juliana, Juliana (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to increase students’ writing ability at descriptive text by using bits and pieces game at MTs PAB 1 Helvetia Medan. This study used class room action research as a methodology. The subjects of this study were 30 students at the eight grade of MTs Helvetia in the academic year 2020/2021. This research used two type data namely quantitative and qualitative. The data quantitative taken by test. On the other hand, to complete the data qualitative were taken by interview, observation sheets, diary notes and documentation. The result of this research showed that there was increasing of students’ writing ability at descriptive text. The mean of the pre test was 59.5 or only 13.33% who success did the test. The mean of first cycle was 70.87 or 36.67% who did the test. And the mean of second cycle was 79.03 or 86.67%. It showed that the mean of second cycle was better than pre-test and first cycle. It can be conclude that bits and pieces game can increase students’ writing ability at descriptive text at eight grade of MTs PAB Helvetia Medan.